An analysis of the determinants of providing business services in Mainland China - Chia-Chi Lee; Huan-Hsuan Tung (Operations Research Perspectives, 2017)
This paper analyzes the factors affecting decision-making on the provision of business services by Taiwanese accounting firms in Mainland China, in order to provide suggestions and managerial implications to accounting firms on decision-making concerning business operations. Logistic regression analysis is conducted, and the empirical model of decision-making on the provision of business services in Mainland China is developed. The dependent variable is whether or not to provide business services in Mainland China; the independent variables are divided into five dimensions: firm attributes, labor structure and allocation, type of professional service, employee contribution, and client diversification. According to the results, when an accounting firm establishes a management consulting firm, has a higher percentage of employees with high educational levels, has a higher percentage of young employees, has a higher percentage of management consulting personnel, and has a higher percentage of financial auditing business revenue, the probability of providing business services in Mainland China will be higher. However, when the percentage of tax service personnel is high and the clients are highly diversified, the probability of providing business services in Mainland China will be lower. Therefore, it is suggested that accounting firms should set up management consulting firms, managers should hire more employees with a master's degree, young employees, and management consulting experience; in addition, the firms should actively expand their services in financial auditing and focus on specialized client groups, which will be more helpful to the accounting firms providing related business services and operational development in Mainland China. The findings can provide references to managers of accounting firms for the evaluation of expanding their business to Mainland China, as well as related decision-making.
Keywords: 330; Mainland China; Business services; Accounting firms